Transcriptional and translational abundance of Bone morphogenetic protein (BMP) 2, 4, 6, 7 and their receptors BMPR1A, 1B and BMPR2 in buffalo ovarian follicle and the role of BMP4 and BMP7 on estrogen production and survival of cultured granulosa cells. (June 2018) - Rajesh, G.; Mishra, S.R.; Paul, A.; Punetha, M.; Vidyalakshmi, G.M.; Narayanan, K.; Bag, S.; Bhure, S.K.; Singh Chouhan, V.; Maurya, V.P.; Singh, G.; Sarkar, Mihir
Abstract: BMPs and their receptors modulate the granulosa cell (GC) function in the follicle of domestic animals. Since little is known on BMPs in the buffalo, the present study was aimed to investigate the expression of BMP2, 4, 6, 7 and their receptors BMPR1A, BMPR1B, BMPR2 in the GC and theca cells (TC) of ovarian follicles and the role of BMP4 and BMP7 on buffalo GC. Follicles were classified into four groups based on size and E2 level in the follicular fluid as follows: (i) Group1(4–6 mm; <0.5 ng/mL) (ii) Group 2 (7–9 mm; 0.5–5 ng/mL) (iii) Group 3 (10-13 mm; 5–40 ng/mL) and (iv) Group 4 (dominant follicle) (>13 mm; >180 ng/mL). The results revealed that except BMP6, BMP2, 4 7 and receptors BMPR1A, BMPR1B and BMPR2 showed a minimum of 1.5–2 fold increase in mRNA expression in the GC of dominant follicle as compared to other follicle classes. In the dominant follicle, a two-fold increase in BMP4 and BMP7 expression was observed in the TC. At 100 ng/mL, the BMP4 and BMP7 either alone or in combination maximally down-regulated CASPASE3 and stimulated the transcripts of PCNA, FSHR and CYP19A1 that was supported by E2 secretion in the granulosa cell culture suggesting their role in cell survival and E2 production. In conclusion, GC and TC of dominant follicles express BMP 2, 4, 6, 7 and their receptors BMPR1A, BMPR1B and BMPR2. BMP4 and BMP7 stimulate E2 production and promote GC survival. Highlights: BMPs and their receptors are expressed in regulated manner during different stages of follicular development in buffalo. BMP4 and BMP7 stimulate granulosa cell steroidogenesis. BMP4 and BMP7 possibly act as a cytoprotective factor and promote granulosa cell survival.